Antibody depletion strategy for the treatment of suspected antibody‐mediated rejection in lung transplant recipients: Does it work?. Issue 3 (1st February 2017) - Vacha, Mary; Chery, Godefroy; Hulbert, Amanda; Byrns, Jennifer; Benedetti, Clark; Finlen Copeland, Catherine Ashley; Gray, Alice; Onwuemene, Oluwatoyosi; Palmer, Scott M.; Snyder, Laurie D.
Abstract: Background: Donor‐specific antibodies (DSAs) after lung transplantation correlate with poor outcomes. The ideal treatment strategy for antibody‐mediated rejection AMR is not defined. Our institution implemented an aggressive multimodality protocol for the treatment of suspected AMR. Methods: Lung transplant recipients with suspected AMR were treated with a standardized protocol of plasma exchange, steroids, bortezomib, rituximab, and intravenous immune globulin. Primary outcome was DSA clearance at 6 months in those alive. Secondary endpoints included preserved allograft function at 6 months, survival at 6 and 12 months and complications due to the protocol. Results: Sixteen lung transplant recipients with documented DSA and allograft dysfunction were included in the analysis. Of the 16 patients, 11 survived to 6 months. Three of those 11 patients (27%) cleared all DSAs within 6 months of the protocol. Four of the 11 patients (36%) had preserved allograft function at 6 months. Overall 12‐month patient survival was 56%. Complications included thrombocytopenia (50%) and abdominal pain or gastrointestinal discomfort (18.7%). Conclusions: This multimodality protocol resulted in clearance of DSAs and preserved lung function in a minority of lung transplant recipients with suspected AMR surviving to 6 months after therapy. There were significant side effects of the protocol.